Variation in Indonesian Sign Language A Typological and Sociolinguistic Analysis - Palfreyman, Nick (Sign Language Typology [SLT], 2019)
This pioneering work on Indonesian Sign Language (BISINDO) explores the linguistic and social factors that lie behind variation in the grammatical domains of negation and completion. Using a corpus of spontaneous data from signers in the cities of Solo and Makassar, Palfreyman applies an innovative blend of methods from sign language typology and Variationist Sociolinguistics, with findings that have important implications for our understanding of grammaticalisation in sign languages. The book will be of interest to linguists and sociolinguists, including those without prior experience of sign language research, and to all who are curious about the history of Indonesia's urban sign community. Nick Palfreyman is a Leverhulme Early Career Research Fellow at the International Institute for Sign Languages and Deaf Studies (iSLanDS), University of Central Lancashire.